SHARIA BUSINESS INNOVATION MODEL IN ENHANCING SUSTAINABLE ECONOMIC GROWTH - Kholishudin Kholishudin; Shelvyna Rikantasari (Study Program of Sharia Business Management , Faculty of Islamic Economics and Business, 2024)
The primary challenge facing many economies today is achieving sustainable growth while adhering to ethical business practices. This is particularly relevant in the context of Sharia-compliant businesses, which must balance profitability with Islamic principles. Addressing this issue requires innovative business models that can promote both economic and social welfare. This study employs a qualitative research methodology, involving in-depth interviews with key stakeholders in Sharia-compliant businesses, including entrepreneurs, financial experts, and regulators. Data was collected through a series of structured and semi-structured interviews, followed by thematic analysis to identify key patterns and insights. The qualitative approach was chosen to gain a nuanced understanding of the complexities involved in implementing Sharia-compliant business innovations. The findings indicate that Sharia business innovations significantly contribute to sustainable economic growth by fostering financial inclusion and ethical investment. Successful models leverage technology to enhance transparency and efficiency, aligning business operations with Sharia principles while meeting market demands. Additionally, the study reveals that community engagement and education are crucial in promoting widespread acceptance and understanding of Sharia business practices. These innovations not only drive economic growth but also ensure that the benefits are equitably distributed, contributing to social stability. The research underscores the potential of Sharia-compliant business models to serve as a blueprint for sustainable development in various economic contexts.